PHYSICOCHEMICAL INVESTIGATION OF ANTI-COVID19 DRUGS USING SEVERAL MEDICINAL PLANTS - Mollaamin, Fatemeh (Journal of the Chilean Chemical Society, 2022)
Anti-Covid19 through the hydrogen bonding using the physicochemical properties including heat of formation, Gibbs free energy, electronic energy, charge distribution of active parts in the hydrogen bonding, NMR estimation of medicinal ingredients jointed to the database amino acids fragment of Tyr-Met-His as the selective zone of the Covid19, positive frequency and intensity of different normal modes of these structures have been evaluated. The theoretical calculations were done at various levels of theory to gain the more accurate equilibrium geometrical results, and IR spectral data for each of the complex proposed drugs of N-terminal or O-terminal auto-cleavage substrate were individually determined to elucidate the structural flexibility and substrate binding of seven medicinal plants jointed to active site of Covid19 molecule. A comparison of these structures with two configurations provides new insights for the design of substrate-based anti-targeting Covid19. This indicates a feasible model for designing wide-spectrum of anti- Covid19 drugs. The structure-based optimization of these structures has yielded two more efficacious lead compounds, N and O atoms through forming the hydrogen bonding (H-bonding) with potent anti- Covid19. Finally, two medicinal ingredients of apigenine-7-glucoside and demethoxycurcumine jointed to TMH have directed to a Monte Carlo (MC) simulation. The results strongly suggest that the different data observed in the apigenine-7-glucoside and demethoxycurcumine in the solvent is principally due to basis set functions, induced by a change in polarity of the environment. It is clear that an increase in the dielectric constants enhances the stability of these anti-Covid19 drugs.